Das System der klima-genetischen Geomorphologie - Büdel, Julius (ERDKUNDE, 1969)
A natural system of geomorphology is developed, which can be divided into two parts, both based on active form shaping exogenous occurences. Endogenous influences on the formation of the relief sphere (petrovariance, epirovariance, active vulcanism) are not thereby suppressed, but only placed in a proper relationship to active formative exogenous processes. The first part of this system, climatic-dynamic geo morphology, deals with landform processes which are contemporarily exogenous. Besides the special categories of coastal and glacial forms subaerial relief is the primary consideration. The process mechanisms which dominate in this context consist of eight elements of varying and differing importance based on climate: mechanical weathering, chemical decomposition, soil formation, sheet erosion, linear erosion by rivers, transport deposition, quasi-definitive and definitive deposition. Dynamic geomorphology, in an analytical sense, follows the pedologie, hydrologie, morphometric and other physical and chemical concepts and aspects of these eight elements. In this respect not only the measurement and proof techniques of geomorphology and geology are used, but also those of the neighbour disciplines already mentioned. In addition the synthetic problem arises as to how these eight elements work together in a total sense towards the qualitative and quantitative performance of a process mechanism. Both aspects are closely bound up with climatic geomorphology, which systematically investigates the deviations of individual elements and formative mechanisms caused by terrestrial climate. In the sub-aerial division alone, six large ’climate-morphologic’ zones of very different formative strength and efficiency can recognized (Fig. 1). Subdivisions, transitions and convergence phenomena are indicated, but above all the knowledge of the extremes limiting the whole spectrum of processes is striven after. Such extremes include the sub-polar zones of excessive valley formation and the circum-tropical zone of excessive plain formation. As these very complex climatically-determined differences cannot be fully attained in laboratory work the task in this respect is to discover those zones and locations where a particularly clear ’experimental order in Nature’ exists for individual phenomena and processes. The second part, climatic-genetic geomorphology, whose importance has resulted in the whole system being named after it, deals with the analysis of existing relief. This is in large measure not generated by contemporaneously operating processes. Indeed, many relicts of relief formed under past climates are preserved in the crust. In the non-tropics especially, current relief consists, often to an extent of 95 %, of more or less strongly modified relicts of fossil relief generations. The task of climatic genetic geomorphology is to separate out these relicts, to recognize the probable character of the climate at their time of creation and to investigate the operations of the process mechanisms powered by past climates. It must therefore work with methods suitable to this approach: logical-historical indices, large-area geographical comparisons and the clarification of climatic history. Of pre-contemporary relief elements, ’Rumpfflächen’ (rocky ’Altflächen’) are particularly prone to preservation. The ways in which they are fossilised, preserved and ’traditionally modified’ (’worked over’) are explained. The system here presented allows every form element on the land surface to be rationally indicated and allocated to its natural place in a easily-grasped developmental history.